Unveiling altered CD8 T-cell metabolism and homeostatic proliferation behind a low CD4/CD8 ratio in ART-suppressed HIV individuals with normal CD4 recovery - Garrido-Rodríguez, Vanesa; Bulnes-Ramos, Ángel; Olivas-Martínez, Israel; Pozo-Balado, María del Mar; Tejerina-Picado, Francisco; Gutiérrez, Félix; Marco-Sánchez, Cristina; Tiraboschi, Juan Manuel; Castillo-Navarro, Antonia; Bernal, Enrique; Garcia-Guerrero, Maria C.; Puertas, Maria C.; et al. (Frontiers in Immunology, 2025)
BackgroundPeople living with chronic HIV (PLWH) show immune dysfunction, despite viral suppression and normal CD4 recovery, particularly those with low CD4/CD8 ratios. Subjacent cellular alterations of such a reliable marker of clinical progression remain elusive.MethodsCategorization by CD4/CD8 ratio after three year of therapy (R < 0.8/R > 1.2, n = 28/n = 24) and post-hoc reclassification by nadir-CD4 (N ≤ 350/N > 350) were performed in PLWH achieving viral suppression and CD4 ≥ 500. CD4 T cell–associated viral reservoir, as well as metabolism-related gene expression, glucose uptake ability, relative telomere length (RTL), and thymic output for CD4 and CD8 T cells, were determined.ResultsPatients with a CD4/CD8 ratio < 0.8 exhibited reduced CD8 T-cell glucose uptake ability after stimulation (p = 0.007) and trends to shorter RTL (p = 0.093) and to larger CD4-associated viral reservoir (p = 0.068) than R > 1.2. Differently, patients with nadir ≤350 exhibited altered CD4 and CD8 T-cell expression of metabolism-related genes, although no differences in glucose uptake ability, and shorter RTL in both cell subsets, but similar viral reservoir to patients with nadir >350. Remarkably, viral reservoir and both CD4 and CD8 thymic output showed inverse associations (r = −0.623, p = 0.01 and r = −0.661, p = 0.038, respectively).ConclusionA low CD4/CD8 ratio in chronic PLWH stands on a larger viral reservoir in CD4 T cells and metabolic alterations in CD8 T cells, probably related to its exhaustion and compromised effector functionality, and thymic output could contribute to such alterations. Patients with lower nadir-CD4 showed a resting-like CD4 phenotype and a metabolically active CD8 subset, without further viral reservoir extension. Persistence of low CD4/CD8 ratio and low nadir-CD4 counts seems to rely on different immune damage.